Nabywanie nieruchomości gruntowych przez cudzoziemców - Pałasz, Lech (Ground Estates Buying by Foreigners, 2006)
The aim of the article is to show the state of ground estates which are bought by foreigners. This process concerns the years 1990-2004. Data come from the report of Ministry of Interior and Administration and from the literature. The article is finished with practical conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 194-199